THE ESSENCE OF SCHOOL CULTURE IN IMPROVING TEACHER PERFORMANCE IN SMP NEGERI 1 KALIREJO CENTRAL LAMPUNG REGENCY - Rusmiyati (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to discover the essence of school culture in improving teacher performance at SMP Negeri 1 Kalirejo Central Lampung Regency. Data were collected by using observation, interview, and documentation. The subjects of this study were principal, vice principal, teacher, administrative staff, assistant, and security staff. The results of the study showed that school culture namely the regularity of behavior, norms adopted, dominant values, philosophy, rules and climate of school, had an influence on the improvement of teacher performance.